RESPON PENAMBAHAN MINERALKALSIUM,PHOSPOR, MAGNESIUM DAN SULFUR TERHADAP SINTESIS PROTEIN MIKROBA PADA TERNAKKAMBING LOKAL - Triani Adelina (Jurnal Peternakan, 2006)
Microbial growth and various fermentation processes in the rumen require an adequate supply of minerals. Anexperiment was conducted to determine niicrobial protein synthesis in the rumen of goat. Microbial protein synthesis in the rumen was estimated by the excretion of purine derivatives concentration (allantoin, uric acid, xanthine and hypoxanthine) in the urine of 20 goats of local breed. They were randomly allocated into 4 treatments in a Randomized Block Design with 5 replication. Treatments were : A =forages (natural grasses, gliricidia and leucaena) and concentrate (rice brand, com grain and coconut meal); B .. ration A+Ca+P ; C = Ration A+Ca+P+Mg ; D = ration A+Ca+P+S. Ration between forages and concentrates is 60 ; 40 with TDN 53.94% and CP 13.87%. The result showed that there were no effect of mineral Ca, P, Mg and S supplementation on the microbial protein synthesis. The mineral supplementation significantly (P<O.Ol) increased the average daily gain of the goat. Inconclusion, supplementation of Ca, P and S was the best among the treatments.